Vehicle Connectivity and Automation: A Sibling Relationship - Ha, Paul; Chen, Sikai; Du, Runjia; Dong, Jiqian; Li, Yujie; Labi, Samuel (Frontiers in Built Environment, 2020)
The evolution of several scientific advancements has been characterized by the amalgamation of two or more technologies. With respect to vehicle connectivity and automation, recent literature suggests that these two emerging transportation technologies will jointly shape profoundly, the future of transportation. As such, it may be considered useful to revisit the primary concepts of automation and connectivity, and to identify any current and expected future synergies between them. Doing this can help generate knowledge that could be used to justify investments related to systems connectivity and automation. In this paper, we discuss the sibling relationship between the concepts of automation and connectivity in the specific context of road transportation vehicles. This paper discusses the technological concepts of systems automation and systems connectivity, and how they work individually and together to contribute to transportation system efficiency and safety. The paper also discusses the separate and common benefits of the connectivity and automation, and their possible holistic effects in terms of these benefits where they overlap. The paper suggests that vehicle connectivity has immense potential to enhance vehicle automation. Automation, on the other hand, may not significantly promote vehicle connectivity directly, at least not in the short term but possibly in the long term.